Campus quality of life information system : a case study applied to the University of Minho - Rodrigues, Daniel Souto (2009)
When analysing characteristics, form, dimension and organisation of university campi, it can be concluded that they can be seen as urban spaces. This fact is often enhanced due to their location: in urban areas or even merged in the city. In this context, a model for the evaluation of the quality of life based on concepts for urban spaces is presented in this paper. Its main purpose is to provide conceptual bases for the implementation of a decision support system that evaluates the university campus quality of life. The process integrates users’ perception and provides the ability to assess the impact of future interventions on the campus quality of life using scenarios. Those scenarios can be created by a tool included in the system and enabled to express through indicators values updates corresponding to possible changes in campus. The evaluation of the quality of life variation that would result from the scenario execution will serve as a decision support tool for campus management when studying several possibilities.